Their accidental honeymoon - Shroff, Mona (Harlequin special edition, 2023)
"Spending his tropical honeymoon with his lifelong best friend, Rani Mistry, was the balm Param Sheth needed after being jilted on his wedding day. Until an unexpected kiss unleashes emotions long held in check! Param and Rani agree it was a mistake, never to be discussed again. But when Rani declares their (fake) elopement so Param's younger brother can be married, they can't ignore their very real-and very buried-feelings much longer. And as Rani's pretend husband, Param wonders whether it's finally time to make this fantasy come true ..."--